Sistem Pendukung Keputusan dalam Pemilihan Mobil LCGC dengan Metode ELECTRE Berbasis Website - Muhammad Rifqi Maulana Maulana (E-Jurnal Universitas Samudra, 2022)
The need of the general public in Indonesia for four-wheeled vehicles to support transportation from one place to another continues to increase. Each individual has different needs for the type of car they want to own. A car with a different type has a different function. When wanting to own a car, there are many factors that must be considered before buying which often makes an individual confused about the various choices of brands and types available. This is the background for making a decision support system using the electre method.